Studies On Some Genetic And Nongenetic Factors Affecting Lactation Period In Gir Cows - Rajoriya, Ravi; Tomar, S.S.; Saha, D. N.; Rajoriya, Shweta; Kumar, Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A total of 599 records of lactation period on 191 Gir cows maintained at Kasturba Gandhi Memorial Trust, Indore, M. P. over a period of 36 years (1974-2009) were analyzed by least squares technique of fitting constants to estimate the effect of sire, period of calving, season of calving, parity and inbreeding. The overall least squares mean of lactation period was found to be 303.28 ± 5.67 days. The results revealed that sire (p
Keywords: Inbreeding; Gir cows; lactation period